From lectures to flipped classroom: A quasi-experimental crossover study on students’ performance and perceptions in learning histology. - Dr. Kavya; Pitchandy, Dr. Geetha Saraswathy; RangaIyengar , Dr. Ramesh Bindinganabile; LaxmiNarayana, Dr. Sharmadha Kodur; Balakrishnan, Dr . Yogi Anupkumar (Student's Journal of Health Research Africa, 2025)
Background: Anatomy education has traditionally relied on didactic lectures, but innovative approaches such as the flipped classroom are increasingly being explored to promote active learning, engagement, and deeper understanding. Objective: To evaluate the effectiveness of the flipped classroom compared to traditional lectures in teaching histology to first-year MBBS students. Methods: A quasi-experimental crossover study was conducted among 150 first-year MBBS students. Two histology topics (stomach and small intestine) were taught using the flipped classroom and didactic lecture methods. Pre-test, mid-test, and post-test scores were recorded using multiple-choice questionnaires. Group A initially underwent flipped classroom teaching, and Group B didactic lectures for Topic 1, followed by crossover for Topic 2. Statistical analysis was performed using paired and independent t-tests. Results: The participants comprised 150 first-year MBBS students (52% female; mean age 19.4 ± 0.8 years). Both teaching methods significantly improved student performance. Didactic lectures showed greater short-term gains (mean post-test = 9.48 ± 1.33 vs. 8.92 ± 1.73; p < 0.05). The flipped classroom group demonstrated a steady incremental improvement from pre-test (6.98 ± 1.94) to mid-test (7.25 ± 2.17) and post-test (8.92 ± 1.73), confirming progressive learning and retention (p < 0.001). Conclusion: Didactic lectures remain effective for achieving rapid short-term learning gains, whereas the flipped classroom fosters gradual improvement, learner autonomy, and deeper engagement. Recommendations: A blended, context-sensitive approach integrating both lectures and flipped classroom strategies is recommended to optimize learning outcomes in anatomy education. Future studies should assess long-term knowledge retention, adaptability, and the role of technology-enabled blended models across diverse medical curricula.